Validity of PMRI-Based Geometry Teaching Materials for Elementary School Students - Mulbasari, Anggria Septiani; Putri, Ratu Ilma Indra; Zulkardi; Aisyah, Nyimas (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2024)
This research aims to develop PMRI-based teaching materials on the elementary school geometry material that meets valid criteria. The research method used in this research is research-type development studies, with research carried out covering three stages: the preliminary stage, the prototyping stage, and the assessment stage. The technique of data collection using walk-through is done by providing teaching materials to experts, who then give comments as well as a mere view of each content, design, and language. Data analysis techniques are the result of a walk-through with experts analysed descriptively as input used to revise the teaching material, validation of the results of expert validation (expert review), and one-to-one results. The results of the development of PMRI-based teaching materials on the valid elementary school geometry materials are derived from the results of expert validation audits in terms of content, construction, and language and one-to-one audits.